Increased suicide risk of psychiatric patients following the recent utilization of health care services: results from a nationwide cohort study in South Korea - Lee, Ju-Mi; Lee, Junhee; Lim, Jiseun; Park, Soonjoo; Ki, Myung; Kang, Jiwon (Frontiers in Public Health, 2023)
Purpose: This study aimed to examine whether and to what degree the suicide risk of psychiatric patients is associated with psychiatric and non-psychiatric health service utilization. Methods: We selected incident psychiatric patients, including schizophrenia, bipolar disorders, borderline personality disorder, depressive disorders, other affective disorders, and post-traumatic stress disorder patients, in 2007–2010 and followed them up until 2017 based on the data linkage between the Korean National Health Insurance and National Death Registry. We analyzed the time-dependent association between suicide and four types of health service (psychiatric vs non-psychiatric and outpatient vs inpatient) utilization using a time-dependent Cox regression. Results: The suicide risk of psychiatric patients was significantly increased with recent psychiatric and non-psychiatric admission and psychiatric outpatient visits. For example, tThe adjusted suicide hazard ratios for recent outpatient visits were similar to or even higher than those for recent psychiatric admission. The adjusted suicide hazard ratios of schizophrenia patients for psychiatric admission, psychiatric outpatient visits, and non-psychiatric admission within the recent six months were 2.34 (95% confidence interval [CI]: 2.12–2.58, p < 0.001), 2.96 (95% CI: 2.65–3.30, p < 0.001), and 1.55 (95% CI: 1.39–1.74, p < 0.001), respectively. Suicide risk was not associated with recent non-psychiatric outpatient visits in patients, except for the depressive disorders group showing a negative association. Conclusions: Our results highlight the priority of suicide prevention for psychiatric patients in the clinical setting. Additionally, our results warrant the precaution against increased suicide risk of psychiatric patients after psychiatric and non-psychiatric discharge.